The heat exchange Intensification in Nano-homo junction semiconductor materials - Mahmood Jubayer (Engineering and Technology Journal, 2015)
In this work, it was examined mechanisms that control internal cooling device (nano-homojunction diode)depending on thermoelectric Peltier effect, resulting in structures that are optimized thermal management. Peltier coefficient for short-length diode is theoretically investigated. It is found that the cooling power is governed by the carrier concentration, current density and the ratio of n-type region width to p-type region width. It has been determined the optimum value of the cooling power at the junction of ZnO in the optimum density at doping symmetrically on a certain value.The cooling power, temperature difference (temperature between the contact and the junction) and dimensionless figure of merit are found in this material for different thicknesses, then comparing between them. It has been simulated the homojunction diode using a MATLAB software with numerically calculated the Peltier coefficient for each layer in these diodes.It has been found that nano-homojunction introduce a significant improvement in the internal cooling performance.